Misconception Analysis Of Students With The Four-Tier Test Through Tree Thinking On Animaly Classification Concept - Nida Anisa; Aa Juhanda; Jujun Ratnasari (Universitas Negeri Medan, 2021)
Misconceptions are knowledge possessed by individuals/students that are irrelevant or not in accordance with existing concepts. This can affect the learning process about scientific concepts. The purpose of this study was to determine the misconceptions students had in the Animalia classification concept. The method used in this research is quantitative descriptive method. This research was conducted on one of the MA in Sukabumi district. The research subjects were 50 students of class X A and X B. The instrument used was a four-tier test (four-level diagnostic test) which was combined with a thinking tree and consisted of 15 questions. The results showed that students who understood the concept (PK) in the Animalia classification material had a percentage value of 23%. Students who do not understand the concept (TPK) have a percentage value of 7%. Students who understand some of the concepts (PS) have a percentage value of 21%. Meanwhile, students who experienced misconceptions (M) in the Animalia classification material had the highest percentage value when compared to other categories, namely 49%. Based on these data, it can be seen that the misconceptions that students have on the Animalia classification concept fall into the medium category.